The Cultural Meaning of Ageing: Community Health Posts as Psychosocial Arenas of Embodiment and Social Relations - Rutmika L.Simanullang; Sri Alem Br. Sembiring (Talenta Publisher, 2026)
This article explores how community-based health service posts in Indonesia for ageing individuals – called Posyandu Lansia – become an arena for health care, and how local sociocultural practices shape their self-understanding of ageing. The study employed a qualitative ethnographic approach, with data collection techniques including participant observation, in-depth interviews with ageing individuals at the Posyandu and in their homes, and field documentation. Data analysis was ongoing throughout the research, including visits to the homes of ageing individuals, triangulation, and analysis of sociocultural issues from field notes. The results indicate that Posyandu Lansia is understood emically by ageing individuals not only as a place for routine health services, but also as a space for social interaction, sharing experiences, motivating one another, receiving emotional support, and affirming self-worth. In this context, Posyandu becomes a space for social relations for them. These situational and contextual conditions confirm the research findings that Posyandu Lansia not only plays a role in maintaining physical health but also operates in a psychosocial and cultural arena that shapes the meaning of becoming an ageing individual, making oneself valuable by forming an ageing community institutionally supported by the state